Radio Access Network Traffic Forecast Analysis for Mobile Network Operators in Anticipation of 5G - Ali Sarfaraz; Heikki Hämmäinen (International Telecommunications Society (ITS), 2019)
The forecast provides a view of how 3G, 4G, and 5G data traffic volumes will evolve over a 5-year period, reflecting the growth of 4G adoption together with operator strategies related to content and data monetisation. Combined with the mobile connections forecast, it provides a view of total network data traffic along with traffic per connection, split explicitly for each radio access technology. Data Collection inputs: 1. Current number of mobile connections as reported by Operator 2. Mobile connection forecast from GSMA with adjustments to reflect competitive impact not considered by the GSMA methodology 3. Historic data traffic volumes as reported by Operators, or if unavailable then Supplier assumptions based on regulator and/or competitor reported data Data Analysis is based on: 1. Data traffic forecast for 5-year period: total, per connection, growth rate, for 3G/4G/5G/combined 2. Difference in data usage between 3G,4G, 5G over time 3. Mobile connection forecast for 5-year period 4. Impact of content evolution, e.g. adoption of higher bandwidth video.
Keywords: 330